Complaint information system and legal education related to violence againts children and women - Roy, Andi; Arridha, Riyadh (Jurnal Mandiri IT, 2025)
Violence against children and women remains a significant societal issue in Indonesia, impacting victims physically, mentally, and economically. Challenges in addressing this include low legal awareness, limited access to reporting mechanisms, and insufficient information about victims' rights. This research aimed to develop an information system to mitigate these challenges by providing a platform for easy complaint filing and accessible legal education. The system, developed using the Waterfall Method and tested with Blackbox testing, incorporates key features such as login, account registration, a homepage, legal education modules, complaint filing, complaint status tracking, and user account management. The successful testing of these features demonstrates the system's potential to improve access to justice, enhance public understanding of legal rights, and ultimately contribute to more effective handling of violence against children and women in Fakfak.